2018
DOI: 10.1038/s41388-017-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic tyrosine kinase Lyn impairs the pro-apoptotic function of Bim

Abstract: Phosphorylation of Ser/Thr residues is a well-established modulating mechanism of the pro-apoptotic function of the BH3-only protein Bim. However, nothing is known about the putative tyrosine phosphorylation of this Bcl-2 family member and its potential impact on Bim function and subsequent Bax/Bak-mediated cytochrome c release and apoptosis. As we have previously shown that the tyrosine kinase Lyn could behave as an anti-apoptotic molecule, we investigated whether this Src family member could directly regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Furthermore, activation of AKT downstream of LYN has been linked to ubiquitination and degradation of the p53 protein (Dos Santos et al, 2013; Iqbal et al, 2010) and this would enable functional suppression of the p53 pathway in BRCA1 mutant cells prior to genetic pathway suppression. Indeed, there is some evidence that LYN is generally anti-apoptotic (Aira et al, 2018) and this warrants further investigation in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of AKT downstream of LYN has been linked to ubiquitination and degradation of the p53 protein (Dos Santos et al, 2013; Iqbal et al, 2010) and this would enable functional suppression of the p53 pathway in BRCA1 mutant cells prior to genetic pathway suppression. Indeed, there is some evidence that LYN is generally anti-apoptotic (Aira et al, 2018) and this warrants further investigation in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Using short interfering RNA to silence LYN expression inhibited the proliferation, migration, and invasion of gastric cancer cells [ 20 ]. Moreover, previous studies showed that the molecular mechanism of the mitochondrial apoptosis pathway is negatively regulated by LYN; this regulation possibly contributes to the transformation of tumor cells and their chemotherapeutic resistance [ 21 ]. Therefore, LYN is thought to be a potential therapeutic target for a variety of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine and their chemotherapeutic resistance [21]. Therefore, LYN is thought to be a potential therapeutic target for a variety of malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Case Studies Application of quantitative structure-activity relationship in structure elucidation of Lyn kinase inhibitors The generalized linear model (GLM) and the artificial neural network (ANN) QSAR models were combined with structural analysis in order to define pharmacophore of Lyn kinase inhibitors (Naboulsi et al, 2018). Lyn kinase is a member of the Src family of tyrosine kinases that was found to be correlated with chemotherapeutic resistance of cancer cells in patients with CML (Chakraborty et al, 2013;Aira et al, 2018). Derived pharmacophore for the inhibition of Lyn kinase suggested the presence of planar heterocyclic ring that contains HBD and HBA, a spacer that allows free bond rotation and central hydrophobic area that is linked to the aromatic ring substituted with lipophilic groups.…”
Section: Ligand-based Methods In Drug Designmentioning
confidence: 99%